Lithium ion secondary battery
By using an improved silicon carbon material and lithium cobalt oxide combination in lithium-ion batteries, the problem of insufficient cycling stability and fast charging capacity of high-energy-density batteries at high voltages is solved, and high energy density, excellent cycling stability and fast charging capacity are achieved.
Patent Information
- Application Number
- CN202411995750.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-12-31
AI Technical Summary
Existing high-energy density lithium-ion batteries have poor cycle stability and insufficient fast charging capabilities at high voltages.
Silicon carbon material is used as the negative electrode active substance, and the average particle size and structure of the silocarbon material are adjusted to improve its conductive properties. At the same time, lithium cobalt oxide is used as the positive electrode active substance, and the lattice structure of lithium cobalt oxide is stabilized by regulating the content of elements Al and Si, as well as the content of 1,3,6-hexane trinitrile in the electrolyte.
It achieves both high energy density, excellent cycle stability and fast charging capability.
Smart Images

Figure CN119890406A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a lithium-ion secondary battery. Background Art
[0002] Lithium-ion batteries have great potential in electronic devices, electric vehicles, etc. Current technology is committed to improving the energy density of batteries. Since silicon-based materials have a higher theoretical specific capacity (about 3600mAh / g), which is much higher than the theoretical specific capacity of graphite materials (about 370mAh / g), using silicon-based materials as negative electrode active materials is considered to be the key to improving battery energy density. At the same time, the capacity of the positive electrode needs to be improved to match the high theoretical specific capacity of silicon-based materials. Therefore, using lithium cobalt oxide as the positive electrode active material and increasing the battery's charge cut-off voltage are more effective methods to increase the capacity of the positive electrode.
[0003] However, at high voltage (charge cut-off voltage ≥ 4.48V), the lattice structure of lithium cobalt oxide will collapse, resulting in poor cycle stability of the battery. In addition, due to the poor conductivity of silicon-based materials themselves, when silicon is added to the negative electrode, the fast charging ability of the battery is poor.
[0004] Therefore, it is necessary to simultaneously improve the cycle stability and fast charging capability of high energy density batteries. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems of poor cycle stability and fast charging capability of high energy density batteries in the prior art, and provide a lithium ion secondary battery. The lithium ion secondary battery of the present invention (hereinafter referred to as the battery) uses silicon-carbon material as a negative electrode active material and lithium cobalt oxide as a positive electrode active material, and can achieve high energy density at a higher charging cut-off voltage (e.g., ≥4.48V). At the same time, in view of the problem of poor electrical conductivity of silicon-based materials, the silicon-carbon material is improved so that the silicon-carbon material includes primary spherical particles, and by regulating the average particle size of the primary spherical particles, the electrical conductivity of the silicon-carbon material is improved, thereby improving the fast charging capability of the battery. In addition, by regulating the content of the element Al in lithium cobalt oxide, and the relationship between the content of the element Si and the content of 1,3,6-hexane trinitrile in the electrolyte, the lattice structure of lithium cobalt oxide is stabilized, thereby improving the cycle stability of the battery.
[0006] The invention provides a lithium ion secondary battery, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte; the charging cut-off voltage of the lithium ion secondary battery is ≥4.48V; the positive electrode sheet comprises a positive electrode active coating, the positive electrode active coating comprises a positive electrode active substance, the positive electrode active substance comprises lithium cobaltate, the lithium cobaltate comprises element Al, and the mass content c1 of element Al in the positive electrode active coating is 6000ppm-15000ppm; the negative electrode sheet comprises a negative electrode active coating, the negative electrode active coating comprises a negative electrode active substance, and the negative electrode active substance comprises a silicon-carbon material; the mass content c2 of element Si in the negative electrode active coating is 1.5%-16%; the silicon-carbon material comprises primary spherical particles, and the average particle size of the primary spherical particles is 1μm-6μm; the electrolyte comprises 1,3,6-hexane trinitrile; the mass content c3 of 1,3,6-hexane trinitrile in the electrolyte and the mass content c2 of element Si in the negative electrode active coating satisfy: 0.63≤c2 / c3≤15.
[0007] The commonly used silicon-carbon materials are block-shaped and have an average particle size of about 6μm-12μm. The relatively large average particle size results in poor conductivity of the particles. And because the hardness of the silicon-carbon material is relatively large, its compaction density is relatively small, which makes it difficult to match the energy density requirements of the system with a silicon content of more than 5% in the negative electrode active coating, that is, the improvement in battery energy density is limited. The silicon-carbon material using primary spherical particles with an average particle size of 1μm-6μm not only has a high silicon content, that is, the silicon content in the negative electrode active coating is as high as 1.5%-16%, which can significantly improve the energy density of the battery; and its small particle size can improve the overall conductivity of the negative electrode sheet, thereby increasing the charging speed of the battery.
[0008] As the upper limit of battery charging voltage increases, the potential on the positive electrode side also increases, which poses a greater challenge to the stability of the lithium cobalt oxide lattice structure. On the one hand, the element Al can form an Al-O bond with the element O in lithium cobalt oxide, which has a larger bond energy, thereby effectively inhibiting the escape of lattice oxygen; on the other hand, Al 3+The stability in the octahedral structure of lithium cobalt oxide is stronger, which makes it more difficult to transform lithium cobalt oxide into a monoclinic system, thereby reducing the kinetics of monoclinic formation and inhibiting the phase change of lithium cobalt oxide. Therefore, by regulating the mass content of element Al in the positive electrode active coating, the effect of stabilizing lithium cobalt oxide can be achieved. However, it does not mean that the greater the content of element Al, the better. This is because when the content of element Al increases, the gram capacity of lithium cobalt oxide will be reduced, thereby affecting the overall energy density of the battery. Therefore, it is necessary to regulate the mass content of element Al in the positive electrode active coating. When a specific range is met, it can ensure that the positive electrode sheet can work stably at high voltage (for example, 4.48V and above), and ensure that the positive electrode sheet has sufficient capacity to play, and will not cause a loss of energy density due to excessive mass content of element Al.
[0009] The above scheme can improve the fast charging capability of the battery, and can improve the cycle stability of the battery to a certain extent, but the improvement in cycle stability has not reached expectations. Therefore, it is necessary to further improve the cycle stability of the battery. The cyano functional group (C≡N) in the molecular structure of 1,3,6-hexanetrinitrile can complex the transition metal ions dissolved from the positive electrode sheet and form a stable CEI (Cathode Electrolyte Interphase) film on the surface of the positive electrode sheet. Therefore, adding nitrile additives to the electrolyte can reduce the risk of metal ion dissolution, electrolyte decomposition and corrosion of the positive electrode sheet by the side reaction product hydrogen fluoride under high voltage, thereby further protecting the lattice structure of lithium cobalt oxide. In addition, the inventors of the present invention have found through a large number of targeted studies that the direct cause of the poor stability of lithium cobalt oxide at high voltage is the silicon-carbon material in the negative electrode sheet. This is because the silicon-carbon material has volume expansion / contraction during the battery charge and discharge cycle, resulting in the continuous rupture and reorganization of the SEI (Solid Electrolyte Interphase) film on the surface of the negative electrode sheet, which continuously consumes the active lithium in the battery. With the continuous consumption of active lithium, lithium ions cannot return to the lattice structure of lithium cobalt oxide, resulting in less and less lithium in the lattice structure of lithium cobalt oxide, and even by regulating the content of element Al, the structural collapse cannot be prevented. In other words, with the increase of the mass content of element Si in the negative electrode active coating, the consumption of active lithium is aggravated, and the collapse of the lithium cobalt oxide lattice is also aggravated. Therefore, it is necessary to simultaneously regulate the mass content of nitrile additives in the electrolyte and the mass content of element Si in the negative electrode active coating. When the two meet a specific relationship, as the mass content of element Si increases / decreases, the content of nitrile additives in the electrolyte increases / decreases at the same time, at this time, both can effectively enhance the structural stability of the positive electrode sheet. When c2 / c3 is small (for example, less than 0.63), the mass content of nitrile additives is relatively high relative to the mass content of elemental Si. At this time, the excess nitrile additives will not only fail to protect the positive electrode, but will damage the negative electrode. When c2 / c3 is large (for example, greater than 15), the mass content of nitrile additives is relatively low relative to the mass content of elemental Si. At this time, the nitrile additives cannot effectively protect the positive electrode, which will lead to a decrease in the cycle stability of the battery.
[0010] Through the above technical solution, the present invention has at least the following advantages compared with the prior art: the battery of the present invention can have high energy density, excellent cycle stability and fast charging capability.
[0011] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 FIG. 1 is a schematic diagram (top view) of a groove on the surface of a negative electrode sheet in an example of the present invention, wherein: Figure 1 (a) The grooves are arranged continuously; Figure 1 (b) The grooves are arranged in sections.
[0013] Figure 2 FIG. 1 is a schematic diagram of the spacing of grooves in an example of the present invention, wherein Figure 2 (a) is the case where two adjacent long sides are straight and parallel. Figure 2 (b) is the case where two adjacent long sides are straight lines and not parallel. Figure 2 (c) is the case where two adjacent long sides are curved lines.
[0014] Figure 3 FIG. 1 is a schematic diagram of the width of a groove in an example of the present invention, wherein Figure 3 (a)- Figure 3 The two long sides of the groove in (c) are straight lines. Figure 3 The two long sides of the groove in (d) are curved.
[0015] Figure 4 FIG. 1 is a schematic diagram showing the structure of a winding core in an example of the present invention.
[0016] Figure 5 The figure shows a schematic diagram of the structure of the positive electrode sheet in an example of the present invention, wherein Figure 5 (a) is a top view, Figure 5 (b) is a cross-sectional view along the thickness direction.
[0017] Figure 6 FIG. 1 is a schematic top view of the first surface of the positive electrode sheet in an example of the present invention. DETAILED DESCRIPTION
[0018] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0019] The present invention provides a lithium ion secondary battery, which may include a positive electrode sheet, a negative electrode sheet and an electrolyte. The charging cut-off voltage of the lithium ion secondary battery is ≥ 4.48V, for example, 4.48V, 4.5V or 4.53V. The term charging cut-off voltage has a conventional meaning in the art, and generally refers to the maximum voltage value that the battery can safely reach during charging.
[0020] In the present invention, the positive electrode sheet may include a positive electrode active coating. The positive electrode active coating may include a positive electrode active material, and the positive electrode active material may include lithium cobalt oxide. The lithium cobalt oxide contains the element Al, and the mass content c1 of the element Al in the positive electrode active coating is 6000ppm-15000ppm, for example, 6000ppm, 7000ppm, 8000ppm, 9000ppm, 10000ppm, 11000ppm, 12000ppm, 13000ppm, 14000ppm or 15000ppm.
[0021] In one example, c1 is 6500 ppm-12000 ppm.
[0022] In the present invention, the mass content c1 of the element Al in the positive electrode active coating can be obtained by testing by conventional methods in the art, for example, using an inductively coupled plasma-optical emission spectrometer (ICP-OES). The specific testing method is as follows: the battery is discharged to 0% SOC, the positive electrode sheet is disassembled and taken out, and immersed in a dimethyl carbonate (DMC) solvent for 12 hours; then the DMC solvent is used for elution to remove the lithium salt attached to the positive electrode sheet, and the positive electrode active coating is gently scraped off from the surface of the positive electrode current collector after calcination at 400° C. in a muffle furnace for 3 hours, and the mass content of the Al element is measured by ICP-OES (in ppm, i.e., one part per million). The specific operation method is performed in accordance with GB / T 30902-2014.
[0023] In the present invention, the chemical formula of lithium cobalt oxide can be Li d Co e M 3 f O2, where 0.8≤d≤1.05, 0.85≤e<1, 0 <f≤0.15,M 3Including at least one of Al, Mg, Ti, Y, La, Ga, Ge, Sn, Si, Zr, Ca, Sb, In, Ni and Mn. Lithium cobalt oxide may include first particles and second particles, the average particle size of the first particles may be 0.3μm-7μm (for example, 0.3μm, 0.5μm, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm or 7μm), and the average particle size of the second particles may be 7.5μm-40μm (for example, 7.5μm, 10μm, 15μm, 20μm, 25μm, 30μm, 35μm or 40μm). Using lithium cobalt oxide with first particles and second particles having different average particle sizes can directly affect the filling effect of lithium cobalt oxide powder during compression by controlling the difference in particle size distribution, thereby affecting the compaction density and electronic conductivity of lithium cobalt oxide, which is beneficial to improving the overall energy density and fast charging capability of the battery.
[0024] In the present invention, the average particle size of the first particles and the average particle size of the second particles can be tested and obtained by conventional methods in the field. For example, after the battery is discharged to 0% SOC, the positive electrode sheet is disassembled and taken out, and then soaked in DMC solvent for 12 hours, and then rinsed with DMC solvent to remove the lithium salt attached to the positive electrode sheet. After calcination at 400°C in a muffle furnace for 3 hours, the positive electrode active coating is gently scraped off the surface of the positive electrode current collector, and tested using a laser particle size analyzer. The particle size range of the first particle and the second particle can be obtained through the obtained curve.
[0025] In the present invention, the negative electrode sheet may include a negative electrode active coating. The negative electrode active coating may include a negative electrode active material, and the negative electrode active material may include a silicon-carbon material. The silicon-carbon material refers to a composite material including elemental carbon and elemental silicon, for example, a material formed by silicon or partially oxidized silicon filled (including partially filled or completely filled) in the pores of porous carbon.
[0026] In the present invention, the mass content c2 of element Si in the negative electrode active coating can be 1.5%-16%, for example, 1.5%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15% or 16%.
[0027] In one example, c2 is 3%-11%.
[0028] In the present invention, the mass content c2 of element Si in the negative electrode active coating can be obtained by testing by conventional methods in the art, for example, after the battery is discharged to 0% SOC, the negative electrode sheet is disassembled and taken out, and after being soaked in DMC solvent for 12 hours, it is then rinsed with DMC solvent to remove the lithium salt attached to the negative electrode sheet, and then the negative electrode sheet is treated at 400°C in an inert atmosphere for 2 hours after drying (for example, in a tubular furnace, under nitrogen or argon atmosphere), and the negative electrode active coating can be peeled off from the negative electrode current collector, and the negative electrode active coating is collected as a test sample. Using a thermogravimetric analyzer (for example, a TGA 550 thermogravimetric analyzer), the test sample amount is 5mg-15mg, and the temperature is increased from room temperature (25°C) to 900°C at a heating rate of 10°C / min in an air or oxygen atmosphere, and kept at 900°C for 40min, so that the non-silicon components in the negative electrode active coating are volatilized while the silicon can be fully oxidized to silicon dioxide. The remaining substance is the ash of the negative electrode active coating. The mass content of element Si in the negative electrode active coating can be calculated based on the mass of the ash. The calculation formula is as follows: mass content of element Si in the negative electrode active coating = 7×mass of ash / (15×mass of test sample).
[0029] In the present invention, the mass content of element Si in the silicon-carbon material can be 30%-80%, for example, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75% or 80%.
[0030] In the present invention, the silicon-carbon material may include primary spherical particles. The average particle size of the primary spherical particles may be 1 μm-6 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm or 6 μm.
[0031] In one example, the average particle size of the primary spherical particles is 3 μm-5 μm.
[0032] In the present invention, the average particle size of the primary spherical particles can be obtained by testing conventional methods in the art, for example, after the battery is discharged to 0% SOC, the negative electrode sheet is disassembled and taken out, and after being soaked in a DMC solvent for 12 hours, it is then rinsed with a DMC solvent to remove the lithium salt attached to the negative electrode sheet, and the negative electrode sheet is cut using an argon ion milling instrument CP laser, and then observed using a SEM (using a high voltage mode (Back-scattered Electrons BSE)). In this mode, the contrast of the silicon-carbon material is brighter (which can be used to distinguish the graphite material and the conductive agent in the negative electrode active coating), and at least 20 primary spherical particles are randomly selected at a 5K magnification, and the particle size of each primary spherical particle is measured to take the average value. If the number of primary spherical particles is less than 20 at a 5K magnification, then a mirror image is taken until 20 primary spherical particles are measured.
[0033] In the present invention, the electrolyte may include 1,3,6-hexanetricarbonitrile (HTCN).
[0034] In the present invention, the mass content c3 of HTCN in the electrolyte and the mass content c2 of element Si in the negative electrode active coating satisfy: 0.63≤c2 / c3≤15, for example, 0.63, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 or 15.
[0035] In one example, 1≤c2 / c3≤7.4.
[0036] In one example, 2≤c2 / c3≤4.
[0037] In the present invention, the mass content c3 of HTCN in the electrolyte may be 0.5%-5%, for example, 0.5%, 1%, 2%, 3%, 4% or 5%.
[0038] In the present invention, the mass content c3 of HTCN in the electrolyte can be measured by conventional methods in the art, such as gas chromatography (GC).
[0039] In the present invention, the electrolyte may further include other nitrile additives, such as acetonitrile, propionitrile, butyronitrile, succinonitrile, malononitrile, glutaronitrile, adiponitrile, pimelonitrile, suberonitrile, sunflower dinitrile, 1,2-bis(2-cyanoethoxy)ethane, 1,3,5-pentanetricarbonitrile, 1,2,3-propanetricarbonitrile, 1,2,6-hexanetricarbonitrile, 1,2,3-tris(2-cyanoethoxy)propane, 1,2,4-tris ...2,4-tris(2-cyanoethoxy)ethane, 1,3,5-pentanetricarbonitrile, 1,2,3-propanetricarbonitrile, 1,2,6-hexanetricarbonitrile, 1, ethoxy) butane, 1,1,1-tris(cyanoethoxymethylene)ethane, 1,1,1-tris(cyanoethoxymethylene)propane, 3-methyl-1,3,5-tris(cyanoethoxy)pentane, 1,2,7-tris(cyanoethoxy)heptane, 1,2,6-tris(cyanoethoxy)hexane, 1,2,5-tris(cyanoethoxy)pentane, ethylene glycol bis(propionitrile), hexafluorocyclotriphosphazene, pentafluoroethoxycyclotriphosphazene, pentafluoro Phenoxy cyclotriphosphazene, 1,4-dicyano-2-butene, p-fluorobenzonitrile, p-methylbenzonitrile, 2-fluoroadiponitrile, 2,2-difluorosuccinonitrile, 1,5-dicyanopentane, 1,6-dicyanohexane, 1,7-dicyanoheptane, 1,8-dicyanooctane, 1,9-dicyanononane, 1,10-dicyanodecane, 1,12-dicyanododecane, 2,2,4,4-tetramethylglutaronitrile, 1,4-dicyanopentane At least one of 2,6-dicyanoheptane, 2,7-dicyanooctane, 2,8-dicyanononane, 1,6-dicyanodecane, tetramethylsuccinonitrile, 2-methylglutaronitrile, 2,4-dimethylglutaronitrile, 3,5-dioxa-heptanenitrile, 1,4-bis(cyanoethoxy)butane, ethylene glycol di(2-cyanoethyl)ether, tricyanobenzene, acrylonitrile, crotononitrile, trans-butenedinitrile, glycerol trinitrile and trans-hexenedinitrile.
[0040] In the present invention, the positive electrode active coating may further include a lithium supplement agent.
[0041] Adding a lithium supplement to the positive electrode active coating can effectively compensate for the irreversible capacity loss of batteries with high silicon content (for example, the mass content of element Si in the negative electrode active coating is ≥5%) during the first charge and discharge process. At the same time, the remaining lithium ions can also continuously stabilize the structure of the lithium cobalt oxide surface during the subsequent charge and discharge cycles of the battery, further alleviating the collapse of the lattice structure of lithium cobalt oxide caused by lithium ion deintercalation, thereby improving the energy density of the battery and ensuring the charging performance of the battery throughout its service life.
[0042] In the present invention, the lithium supplement comprises a chemical formula of Li 5+x Fe y M 1 z The substance and / or chemical formula of O4 is Li 2± a Ni b M cO2; wherein, -0.5≤x≤5 (for example, -0.5, 0, 1, 2, 3, 4 or 5), 0.8≤y≤1.2 (for example, 0.8, 0.9, 1, 1.1 or 1.2), 0≤z≤1 (for example, 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1), M 1 Including at least one of Mo, Nb, Ti, Zr, Ni, Y, Mn, Cu, Mg and Zn; 0≤a≤0.5 (for example, 0, 0.1, 0.2, 0.3, 0.4 or 0.5), 0≤b≤1 (for example, 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1), 0≤c≤1 (for example, 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1), M 2 Includes at least one of Mo, Nb, Ti, Zr, Fe, Y, Mn, Cu, Mg and Zn.
[0043] In one example, the lithium supplement includes Li2NiO2 and / or Li5FeO4.
[0044] In the present invention, the element M 1 and / or the element M 2 The mass content c4 in the positive electrode active coating can be 900ppm-7000ppm, for example, 900ppm, 1000ppm, 1500ppm, 2000ppm, 2500ppm, 3000ppm, 3500ppm, 4000ppm, 4500ppm, 5000ppm, 5500ppm, 6000ppm, 6500ppm or 7000ppm.
[0045] In one example, c4 is 1600ppm-6000ppm.
[0046] Since the lithium supplement agent has poor conductivity and poor environmental adaptability, it is easy to react with moisture and carbon dioxide in the air, thereby affecting the stability of the positive electrode sheet. Therefore, it is necessary to control the content of the lithium supplement agent in the positive electrode active coating. C4 can reflect the content of the lithium supplement agent in the positive electrode active coating. When c4 is within a specific range, the lithium supplement agent can supplement the first coulomb efficiency (hereinafter referred to as the first efficiency) and continuously supplement lithium ions during the battery cycle to further improve the stability of the lithium cobalt oxide lattice structure, and will not produce many side reactions to affect the stability of the positive electrode sheet. If c4 is small (for example, less than 900ppm), the content of the lithium supplement agent is too small and cannot play a role in improving the lattice structure of lithium cobalt oxide; if c4 is large (for example, greater than 7000ppm), the content of the lithium supplement agent is too high, which not only cannot guarantee its own stability, but also seriously affects the effective period of use of the lithium supplement agent in the actual production process and causes the stability of the positive electrode sheet structure to deteriorate; it also causes the fast charging performance of the battery to deteriorate.
[0047] In the present invention, the element M 1 and / or the element M 2 The mass content c4 in the positive electrode active coating can be obtained by conventional methods in the art, such as using ICP-OES. The specific testing method is as follows: the battery is discharged to 0% SOC, the positive electrode sheet is disassembled and taken out, and then immersed in DMC solvent for 12 hours; then the DMC solvent is used to rinse to remove the lithium salt attached to the positive electrode sheet, and the positive electrode active coating is gently scraped off from the surface of the positive electrode current collector after calcination at 400° C. in a muffle furnace for 3 hours, and the element M is measured by ICP-OES. 1 and / or element M 2 The mass content (in ppm) of the product shall be measured according to GB / T 30902-2014.
[0048] In the present invention, the mass content of c4 and element Si in the negative electrode active coating layer c2 satisfies: 0.005≤c4 / c2≤0.19, for example, 0.005, 0.006, 0.007, 0.008, 0.009, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18 or 0.19.
[0049] In one example, 0.028≤c4 / c2≤0.093.
[0050] The first efficiency of the battery decreases with the increase of the mass content of element Si in the negative electrode active coating. At this time, more lithium supplements are needed to compensate for the adverse effects of silicon on the first efficiency of the battery. When the two do not match, there will be a situation where the lithium supplement is relatively more than the silicon-carbon material. At this time, too much lithium supplement will cause the fast charging performance and stability of the battery to deteriorate; or there will be a situation where the silicon-carbon material is relatively more than the lithium supplement. At this time, too little lithium supplement cannot effectively supplement the first effect, and it is impossible to further improve the lattice stability of lithium cobalt oxide through continuous lithium supplementation, which is also not conducive to improving the stability of the battery. Therefore, it is necessary to regulate the relationship between the two. When a specific relationship is met, the battery can have a high first efficiency and cycle stability while ensuring fast charging performance.
[0051] In the present invention, the OI value of the negative electrode active coating can be 10-30, for example, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29 or 30.
[0052] In one example, the OI value of the negative electrode active coating is 12-17.
[0053] In the present invention, the OI value of the negative electrode active coating can be obtained by testing by conventional methods in the art, for example, after the battery is discharged to 0% SOC, the negative electrode sheet is disassembled and taken out, and then soaked in DMC solvent for 12 hours, and then rinsed with DMC solvent to remove the lithium salt attached to the negative electrode sheet, and the negative electrode active coating is tested using an X-ray powder diffraction instrument (such as Shimadzu XRD-6100) to obtain a diffraction spectrum, and the intensity of the (004) peak at 2θ of 54°-55° is recorded as I 004 The intensity of the (110) peak with 2θ of 77°-78° is recorded as I 110 , OI value is I 004 / I 110 .
[0054] The OI value of the negative electrode active coating can affect the expansion rate of the negative electrode sheet in the thickness direction to a certain extent. Specifically: The OI value of the negative electrode active coating represents the overall orientation of the negative electrode active material. The smaller the OI value, the smaller the expansion rate of the negative electrode active material in the thickness direction of the battery. By regulating the OI value of the negative electrode active coating, the cycle stability of the battery can be further improved.
[0055] In the present invention, the sphericity s of the primary spherical particles may be 0.7-1, for example, 0.7, 0.8, 0.9 or 1.
[0056] In one example, the sphericity s of the primary spherical particles is 0.8-0.95.
[0057] In the present invention, the sphericity s of the primary spherical particles can be tested by conventional methods in the art, for example, after the battery is discharged to 0% SOC, the negative electrode sheet is disassembled and taken out, and after being soaked in DMC solvent for 12 hours, the negative electrode sheet is rinsed with DMC solvent to remove the lithium salt attached to the negative electrode sheet, and then the negative electrode active coating is rinsed off from the negative electrode current collector with deionized water, and the filtrate is removed by centrifugation after ultrasound, and dried, and the obtained powder is observed by SEM (high voltage mode). The image of the primary spherical particles of silicon-carbon material in the SEM mirror image under a certain magnification (for example, 2500 times) is analyzed by image processing software (for example, Image Pro Plus), and at least 10 primary spherical particles of silicon-carbon material in the mirror image are selected to obtain the perimeter and area of each particle, and the perimeter equivalent radius and area equivalent radius are calculated respectively, then the sphericity = area equivalent radius / perimeter equivalent radius, and the average value is taken.
[0058] In the present invention, the outer surface of the negative electrode active coating may have a first concave portion. The negative electrode sheet includes a negative electrode current collector and the negative electrode active coating located on at least one side of the negative electrode current collector. The outer surface of the negative electrode active coating refers to the surface of the negative electrode active coating that is away from the negative electrode current collector.
[0059] In the present invention, the spacing g of the first recesses and the sphericity s of the primary spherical particles satisfy: 0.4≤g×s≤2, wherein the spacing g of the first recesses is in mm, for example, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 or 2.
[0060] In one example, 0.6≤g×s≤1.5.
[0061] The first concave portion on the surface of the negative electrode active coating can provide a certain release space for the volume expansion of the negative electrode active material, reduce the extension of the negative electrode current collector caused by the volume expansion of the negative electrode active material, and help to further improve the cycle stability of the battery. When the spacing of the first concave portions is small, the first concave portions on the surface of the negative electrode active coating are denser, and more silicon-carbon materials will be exposed. On the contrary, when the spacing of the first concave portions is large, less silicon-carbon materials are exposed. Generally, the lower the sphericity of the silicon-carbon material, the more defects on its surface, and it may have more protrusions and depressions. And because the hardness of the silicon-carbon material is large, when its sphericity is lower, the protrusions and depressions on the surface may puncture the diaphragm and cause a short circuit, or may cause extrusion to the positive electrode sheet, resulting in a greater risk of positive electrode sheet fracture. As the sphericity of the silicon-carbon material increases, it becomes less sharp. At this time, the spacing of the first concave portions can be appropriately reduced (more silicon-carbon materials can be appropriately exposed). Therefore, by regulating the relationship between the two, while ensuring the safety of the battery, the negative electrode side dynamics can be improved, thereby improving the fast charging performance of the battery.
[0062] In the present invention, the first concave portion may include a concave hole or a groove. The first concave portion may be obtained by laser drilling or wire punching technology. The groove may be arranged continuously or in sections. Figure 1 FIG. 1 is a schematic diagram (top view) of a groove on the surface of a negative electrode sheet in an example of the present invention, wherein: Figure 1 (a) The grooves are arranged continuously; Figure 1 (b) The grooves are arranged in sections. As can be seen from the figure, the surface of the negative electrode sheet (i.e., the outer surface of the negative electrode active coating) has several grooves. Figure 1 In (a), the grooves are continuously arranged in the width direction of the negative electrode sheet. Figure 1 In (b), the grooves are arranged in sections in the width direction of the negative electrode sheet. It can be understood that Figure 1 Only the case where the groove is arranged along the width direction of the negative electrode sheet is given, and the groove can also be arranged along the length direction of the negative electrode sheet.
[0063] In the present invention, the spacing g of the first recesses may be 0.5 mm-5 mm, for example, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1 mm, 1.5 mm, 2 mm, 2.5 mm, 3 mm, 3.5 mm, 4 mm, 4.5 mm or 5 mm.
[0064] In one example, the interval g of the first recesses is 0.8 mm-1.5 mm.
[0065] When the first concave portion is a concave hole, the spacing of the first concave portion refers to the spacing of the concave holes. The spacing of the concave holes has a conventional meaning in the art. It refers to the shortest distance between the edges of two adjacent concave holes on the surface of the negative electrode sheet. The spacing of the concave holes can be obtained by conventional means in the art, such as by selecting all or at least 10 groups of adjacent concave holes through a 3D profilometer, measuring the spacing, and taking the average value.
[0066] When the first recess is a groove, the spacing of the first recess refers to the spacing of the grooves. It is understandable that when there is only one groove on the surface of the negative electrode sheet, there is no spacing of the grooves. The spacing of the grooves has the conventional meaning in this field. The positive projection of the groove on the surface of the negative electrode sheet includes two long sides. The spacing of the grooves refers to the average distance between the two adjacent long sides of two adjacent grooves in the length direction or width direction of the negative electrode sheet. Figure 2 FIG. 1 is a schematic diagram of the spacing of grooves in an example of the present invention, wherein Figure 2 (a) is the case where two adjacent long sides are straight and parallel. Figure 2 (b) is the case where two adjacent long sides are straight lines and not parallel. Figure 2 (c) is the case where two adjacent long sides are curved. Figure 2 In (a), the two adjacent long sides are straight and parallel, so in the width direction, the distance from any point on one long side to the other long side is equal. In this case, the spacing of the grooves is the distance L2 from any point on one long side to the other long side in the width direction. Figure 2 In (b), the two adjacent long sides are straight lines, but they are not set in parallel. Therefore, in the width direction, the distance from any point on one long side to the other long side is not equal. In this case, the spacing of the grooves can be averaged, that is, on a long side, based on the length of the side, 50 points are selected at equal distances (that is, the distance between each point is equal, so that the selection of points can make the calculation result more accurate), and the width L2 corresponding to each point is measured, and the average value is taken to obtain the spacing. Figure 2 In (c), the two adjacent long sides are curved. Therefore, in the width direction, the distance from any point on one long side to the other long side is not equal. In this case, the spacing of the grooves can also be averaged, that is, 50 points are randomly selected on one long side (due to Figure 2 (c) The two long sides are curved, so there is no Figure 2 (b) The relationship between the two long sides, therefore, 50 points can be randomly selected for measurement), and the width L2 corresponding to each point is measured, and the average value is taken to obtain the spacing. The spacing of the grooves can be obtained by conventional means in the art, such as by using a 3D profilometer to test the spacing of all grooves or at least 5 grooves on the surface of the negative electrode active coating and take the average value.
[0067] In the present invention, the depth of the first concave portion may be 5 μm-40 μm, for example, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm or 40 μm.
[0068] In one example, the depth of the first concave portion is 15 μm-30 μm.
[0069] The depth of the first concave portion has a conventional meaning in the art, and refers to the vertical distance from the lowest point in the first concave portion to the surface of the negative electrode sheet. The depth of the first concave portion can be measured by conventional methods in the art, for example, by measuring the depths of all first concave portions or at least 20 first concave portions on the surface of the negative electrode active coating layer using a 3D profilometer, and taking an average value.
[0070] In the present invention, the width of the first concave portion may be 40 μm-200 μm, for example, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 150 μm or 200 μm.
[0071] In one example, the width of the first concave portion is 60 μm-100 μm.
[0072] When the first recess is a recessed hole, the width of the first recessed portion refers to the aperture of the recessed hole. The aperture of the recessed hole has the conventional meaning in this field. When the shape of the orthographic projection of the recessed hole on the surface of the negative electrode sheet is a "regular circle", the aperture of the recessed hole is the diameter of the regular circle; when the shape of the orthographic projection of the recessed hole on the surface of the negative electrode sheet is a non-"regular circle" (such as an ellipse or an irregular curved polygon), the aperture of the recessed hole is the diameter of an equivalent circle with an area equal to that of the non-"regular circle". The aperture of the recessed hole can be obtained by conventional means in this field, such as by using a 3D profilometer to test the apertures of all recessed holes or at least 20 recessed holes on the surface of the negative electrode active coating and take the average value.
[0073] When the first concave portion is a groove, the width of the first concave portion refers to the width of the groove. The width of the groove has a conventional meaning in the art. The width of the groove refers to the average distance from one long side to another long side in the length direction or width direction of the negative electrode sheet. Figure 3 FIG. 1 is a schematic diagram of the width of a groove in an example of the present invention, wherein Figure 3 (a)- Figure 3 The two long sides of the groove in (c) are straight lines. Figure 3 The two long sides of the groove in (d) are curved. Figure 3 (a) and Figure 3In (b), the two long sides are arranged in parallel, so that in the width direction of the negative electrode sheet, the vertical distance from any point on one long side to the other long side is equal. In this case, the width of the groove is the vertical distance L1 from any point on one long side to the other long side in the length direction or width direction of the negative electrode sheet. Figure 3 In (c), the two long sides of the groove are straight lines, but they are not set in parallel. Therefore, in the width direction, the size from any point on one long side to the other long side is not equal. In this case, the width of the groove can be averaged, that is, on one long side, based on the length of the side, 50 points are selected at equal distances (that is, the distance between each point is equal, so that the selection of points can make the calculation result more accurate), and the width L1 corresponding to each point is measured, and the average value is taken to obtain the width of the groove. Figure 3 In (d), the two long sides are curved. Therefore, in the width direction, the distance from any point on one long side to the other long side is not equal. In this case, the width of the groove can also be averaged, that is, 50 points are randomly selected on one long side (due to Figure 3 In (d), the two long sides are curved and do not exist. Figure 3 (c) The relationship between the two long sides, therefore, 50 points can be randomly selected for measurement), and the width L1 corresponding to each point is measured, and the average value is taken to obtain the width of the groove. The width of the groove can be obtained by conventional means in the art, such as by using a 3D profiler to test the width of all grooves or at least 5 grooves on the surface of the negative electrode active coating and take the average value.
[0074] In the present invention, the silicon-carbon material further comprises secondary spherical particles formed by a plurality of the primary spherical particles. The “several” means that the number of the primary spherical particles forming the secondary spherical particles is greater than or equal to 2.
[0075] The conventionally used silicon-carbon material is in block form, and the average particle size is about 6μm-12μm. Therefore, the conductivity is poor, and it is difficult to achieve a large compaction density. The energy density can be improved to a limited extent, and it is not suitable for 5% silicon-doped (that is, the mass content of element Si in the negative electrode active coating is 5%) system batteries. In the present invention, a silicon-carbon material including primary spherical particles is used as the negative electrode active material. Primary spherical particles with smaller particle sizes are beneficial to improving the energy density of the battery; however, due to their smaller particle size and larger specific surface area, the risk of side reactions with the electrolyte is correspondingly increased, and the stability is poor. In order to reduce the occurrence of side reactions between the silicon-carbon material and the electrolyte, secondary spherical particles formed by several primary spherical particles are further added. Secondary spherical particles with larger particle sizes have a smaller specific surface area, so they have a lower risk of side reactions with the electrolyte and better stability.
[0076] In the present invention, the average particle size of the secondary spherical particles can be 3μm-20μm, for example, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm or 20μm.
[0077] In the present invention, the average particle size of the secondary spherical particles can be tested by conventional methods in the art, for example, after discharging the battery to 0% SOC, disassembling and removing the negative electrode sheet, soaking it in DMC solvent for 12 hours, and then rinsing it with DMC solvent to remove the lithium salt attached to the negative electrode sheet, using an argon ion milling instrument CP laser to cut the negative electrode sheet, and then using SEM observation (high voltage mode), measuring at a magnification of 5K, randomly selecting at least 20 secondary spherical particles, measuring the particle size of each secondary spherical particle, and taking the average value. If the number of secondary spherical particles is less than 20 at a magnification of 5K, then take a mirror image again until 20 secondary spherical particles are measured.
[0078] In the present invention, in the negative electrode active coating, the amount of the primary spherical particles accounts for 0.1-0.9 of the total amount of the primary spherical particles and the secondary spherical particles, for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 or 0.9.
[0079] In one example, in the negative electrode active coating, the amount of the primary spherical particles accounts for 0.3-0.8 of the total amount of the primary spherical particles and the secondary spherical particles.
[0080] In the present invention, in the negative electrode active coating, the number of the primary spherical particles and the number of the secondary spherical particles can be tested and obtained by conventional methods in the art, for example, after the battery is discharged to 0% SOC, the negative electrode sheet is disassembled and taken out, and after being soaked in DMC solvent for 12 hours, it is rinsed with DMC solvent to remove the lithium salt attached to the negative electrode sheet, and the negative electrode sheet is cut along the thickness direction of the negative electrode sheet using an argon ion milling instrument CP laser, and then observed using SEM (using high voltage mode) to obtain a mirror image of the cross section of the negative electrode sheet along the thickness direction, and observed at a magnification of 1K, and at least 20 mirror images of different cross sections are selected, and the number of primary spherical particles and the number of secondary spherical particles in each mirror image are counted respectively, and the average value is taken.
[0081] In the present invention, the negative electrode active material may further include a graphite material. The graphite material includes, for example, artificial graphite and / or natural graphite. The graphite material includes secondary particles. The secondary particles are formed by a plurality of primary particles. The “several” means that the number of the primary particles forming the secondary particles is greater than or equal to 2.
[0082] In the present invention, the average particle size of the secondary particles may be 6 μm-20 μm, for example, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm or 20 μm.
[0083] By using a specific graphite material and adjusting the structure and particle size of the graphite material, the graphite material includes secondary particles formed by primary particles, and the average particle size of the secondary particles is 6μm-20μm, which can further improve the energy density of the battery. Compared with the graphite material of the primary particles, the secondary particles of the graphite material with a specific particle size can improve the energy density of the battery. Therefore, the graphite material has a high degree of matching with the specific silicon-carbon material, which is conducive to the improvement of the energy density of the battery.
[0084] In the present invention, the average particle size of the secondary particles can be obtained by testing by conventional methods in the art, for example, after the battery is discharged to 0% SOC, the negative electrode sheet is disassembled and taken out, and after being soaked in DMC solvent for 12 hours, the negative electrode sheet is rinsed with DMC solvent to remove the lithium salt attached to the negative electrode sheet, and the negative electrode active coating is rinsed off from the negative electrode current collector with deionized water, and the filtrate is removed by centrifugation after ultrasonication, and dried, and the obtained sample is dispersed in deionized water containing nonylphenol polyoxyethylene ether (wherein the mass content of nonylphenol polyoxyethylene ether is 0.02%-0.03%) to form a mixture, ultrasonicated for 2 minutes, and then tested using a Malvern particle size tester, and the median particle size Dv50 data obtained is the average particle size of the secondary particles. Due to the specific composition and particle size of the graphite material and the silicon-carbon material in the present invention, the silicon-carbon material has little effect on the average particle size of the secondary particles of the graphite material, so the data obtained by the above test method is the average particle size of the secondary particles.
[0085] In the present invention, the positive electrode sheet may include a positive electrode current collector and the positive electrode active coating located on at least one side of the positive electrode current collector. The length of the positive electrode active coating located on the first surface of the positive electrode current collector is greater than the length of the positive electrode active coating located on the second surface of the positive electrode current collector. It can be understood that when the positive electrode sheet is coated, there are single-sided coating areas and double-sided coating areas. The single-sided coating area is the positive electrode current collector located in the area, and only one side of the surface has the positive electrode active coating; while the double-sided coating area is the positive electrode current collector located in the area, and both sides of the surface have the positive electrode active coating. This leads to the situation that the lengths of the positive electrode active coatings on the two sides of the positive electrode sheet are not equal. In the present invention, the side with a relatively longer length of the positive electrode active coating on the surface of the positive electrode current collector is defined as the first surface, and the side with a relatively shorter length of the positive electrode active coating is defined as the second surface. The area where the projections of the positive electrode active coating located on the first surface and the positive electrode active coating located on the second surface overlap in the thickness direction of the positive electrode sheet is the double-sided coating area, and the area where the above projections do not overlap is the single-sided coating area. Due to the special structure of the wound battery, usually the first surface faces the winding center of the winding core, and the second surface faces away from the winding center of the winding core.
[0086] In the present invention, the surface of the positive electrode active coating on the first surface has a second concave portion, and the surface of the positive electrode active coating on the second surface has a convex portion. Embossing treatment is performed on the surface of the positive electrode sheet to obtain a structure with concave portions on one side and convex portions on the other side.
[0087] The storage location of the electrolyte inside the battery is distributed in the gap between the core and the aluminum-plastic film and in the gap between the electrode layers. Interlayer storage mainly relies on the pores of the electrode and the capillary effect to slowly infiltrate, which takes a longer time and is more difficult to infiltrate than the gap between the core and the aluminum-plastic film. Therefore, the liquid storage capacity of the inner electrode of the core is significantly less than that of the outer electrode. The embossing process is used on the positive electrode to make one side have a concave part and the other side have a convex part, which can provide more liquid storage places, reduce the ion transmission distance, reduce the polarization of the positive and negative electrode sheets, and improve the overall charging speed of the battery.
[0088] In addition, the inventors of the present invention have conducted a stress analysis on the positive electrode active coating facing the winding center and away from the winding center in the winding core, and found that when the second concave portion is provided on the first surface facing the winding center and the convex portion is provided on the second surface away from the winding center, it is not only beneficial to the structural stability of the positive electrode sheet itself, but also can provide a better buffer space for the volume expansion of the negative electrode sheet, which can improve the cycle life of the battery. Figure 4The following is a schematic structural diagram of a core in an example of the present invention. As can be seen from the figure, the core includes a negative electrode sheet 1 and a positive electrode sheet 2. The surface of the positive electrode active coating on the first surface has a second recess, and the surface of the positive electrode active coating on the second surface has a protrusion. The first surface faces the winding center of the core, and the second surface faces away from the winding center of the core.
[0089] In the present invention, the shape of the orthographic projection of the second recess and the protrusion on the surface of the positive electrode sheet is not limited, and it can be a circular shape, an oval shape, a linear shape (including a straight line or a wavy line), a polygonal shape, etc.
[0090] In the present invention, the positive electrode sheet includes a positive electrode tab welding area, a paste coating area, and an empty foil area. The empty foil area refers to the area on the positive electrode current collector where the positive electrode active coating is not coated except for the positive electrode tab welding area. The paste coating area includes a double-sided coating area and a single-sided coating area. As Figure 5 The following is a schematic structural diagram of a positive electrode sheet in an example of the present invention, where Figure 5 (a) is a top view, Figure 5 (b) is a cross-sectional view along the thickness direction. As can be seen from the figure, the positive electrode sheet includes a positive electrode tab welding area 3, a paste coating area 4, and an empty foil area 5, where the paste coating area 4 includes a double-sided coating area 10 and a single-sided coating area 20.
[0091] In one example, the second recess and the protrusion are located in the paste coating area.
[0092] In one example, the second recess and the protrusion are located in the double-sided coating area.
[0093] In one example, the second recess and the protrusion are located in the paste coating area and in the double-sided coating area.
[0094] In the present invention, the distance from the second recess to the edge of the positive electrode tab welding area is w1, 0 mm < w1 ≤ 10 mm, for example, 0.1 mm, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, or 10 mm.
[0095] In the present invention, the distance from the second recess to the edge of the first side of the paste coating area is w2, 2 mm ≤ w2 ≤ 40 mm, for example, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm, 15 mm, 16 mm, 17 mm, 18 mm, 19 mm, 20 mm, 25 mm, 30 mm, 35 mm, or 40 mm. The first side is the side where the positive electrode tab welding area is provided.
[0096] In the present invention, the distance from the second recess to the edge of the second side of the paste application area is w3, where 2 mm ≤ w3 ≤ 25 mm, for example, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm, 15 mm, 16 mm, 17 mm, 18 mm, 19 mm, 20 mm or 25 mm. The second side is the side opposite to the side where the positive tab welding area is provided.
[0097] In the present invention, the distance from the second recess to the edge of the third side of the paste application area is w4, where 0 mm < w4 ≤ 20 mm, for example, 0.1 mm, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm, 15 mm, 16 mm, 17 mm, 18 mm, 19 mm or 20 mm. The third side is the side of the paste application area close to the first winding end.
[0098] In the present invention, the distance from the second recess to the boundary line between the double-sided coating area and the single-sided coating area is w5, where 0 mm < w5 ≤ 20 mm, for example, 0.1 mm, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm, 15 mm, 16 mm, 17 mm, 18 mm, 19 mm or 20 mm.
[0099] By controlling w1, w2, w3, w4 and w5, it is possible to ensure that the positive electrode sheet does not shed powder, which is beneficial to improving the cycle life of the battery.
[0100] As Figure 6 shown in the top view schematic diagram of the first surface of the positive electrode sheet in an example of the present invention, it can be seen from the figure that the first surface has a plurality of second recesses 6. The distance from the second recess 6 to the edge of the positive tab welding area 3 is w1, the distance from the second recess 6 to the edge of the first side of the paste application area 4 is w2, the distance from the second recess 6 to the edge of the second side of the paste application area 4 is w3, the distance from the second recess 6 to the edge of the third side of the paste application area 4 is w4, and the distance from the second recess 6 to the boundary line between the double-sided coating area 10 and the single-sided coating area 20 is w5.
[0101] In the present invention, the depth of the second recess can be 3 μm - 40 μm, for example, 3 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm or 40 μm. The height of the convex portion can be 3 μm - 40 μm, for example, 3 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm or 40 μm.
[0102] In the present invention, the depth of the second concave portion and the height of the convex portion have the conventional meanings in the art, and the depth of the second concave portion refers to the vertical distance from the lowest point in the second concave portion to the surface of the positive electrode sheet. The height of the convex portion refers to the vertical distance from the highest point on the convex portion to the surface of the positive electrode sheet. The depth of the second concave portion and the height of the convex portion can be obtained by testing by conventional methods in the art, for example, by using a 3D profilometer, at least 20 second concave portions or 20 convex portions are selected on the surface of the positive electrode sheet, the depth of each second concave portion is measured, and the average value is taken to obtain the depth of the second concave portion; the height of each convex portion is measured, and the average value is taken to obtain the height of the convex portion.
[0103] In the present invention, the width of the second concave portion may be 0.2 mm to 8 mm, for example, 0.2 mm, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm or 8 mm. The width of the convex portion may be 0.2 mm to 8 mm, for example, 0.2 mm, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm or 8 mm.
[0104] In one example, the width of the second concave portion is 1 mm to 3 mm, and the width of the convex portion is 1 mm to 3 mm.
[0105] In the present invention, when the shape of the projection of the second concave portion in the thickness direction of the positive electrode sheet is a regular circle, the width of the second concave portion is the diameter of the regular circle; when the shape of the projection of the second concave portion in the thickness direction of the positive electrode sheet is a non-"regular circle", the width of the second concave portion is the equivalent diameter of a circle with an area equal to that of the irregular circle. Similarly, when the shape of the projection of the convex portion in the thickness direction of the positive electrode sheet is a regular circle, the width of the convex portion is the diameter of the regular circle; when the shape of the projection of the convex portion in the thickness direction of the positive electrode sheet is a non-"regular circle", the width of the convex portion is the equivalent diameter of a circle with an area equal to that of the irregular circle. The width of the second concave portion and the width of the convex portion can be obtained by conventional methods in the art, for example, by using a 3D profiler, selecting at least 10 second concave portions and 10 convex portions on the surface of the positive electrode sheet, measuring the width of each second concave portion and the width of the convex portion, and taking the average values respectively.
[0106] In the present invention, the spacing of the second concave portions may be 0.5 mm to 8 mm, for example, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm or 8 mm. The spacing of the convex portions may be 0.5 mm to 8 mm, for example, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm or 8 mm.
[0107] In one example, the spacing between the second concave portions is 1 mm to 3 mm, and the spacing between the convex portions is 1 mm to 3 mm.
[0108] In the present invention, the spacing of the second concave portions refers to the shortest distance between the edges of the orthographic projections of two adjacent second concave portions on the surface of the positive electrode sheet, and similarly, the spacing of the convex portions refers to the shortest distance between the edges of the orthographic projections of two adjacent convex portions on the surface of the positive electrode sheet. The spacing of the second concave portions and the spacing of the convex portions can be obtained by testing by conventional methods in the art, for example, by using a 3D profilometer, selecting at least 10 groups of adjacent second concave portions or convex portions on the surface of the positive electrode sheet, measuring the spacing, and taking the average value.
[0109] In the present invention, the positive electrode active coating may further include a positive electrode conductor and a positive electrode binder, and the negative electrode active coating may further include a negative electrode conductor and a negative electrode binder. The positive electrode conductor and the negative electrode conductor may use the conductive agents conventionally used in the art. The positive electrode binder and the negative electrode binder may use the binders conventionally used in the art.
[0110] In the present invention, the lithium ion secondary battery may further include a separator, and the separator may be a conventional one in the art.
[0111] It should be noted that the numerical expressions such as "first" and "second" in the present invention are only used to distinguish different substances or usages, and do not represent the difference in order.
[0112] The present invention will be described in detail below by way of examples. The examples described in the present invention are only a part of the examples of the present invention, rather than all of the examples. Based on the examples in the present invention, all other examples obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0113] In the following examples, unless otherwise specified, all materials used were commercially available analytical grade.
[0114] The following examples are used to illustrate the lithium ion secondary battery of the present invention.
[0115] Example 1
[0116] Prepare the battery as follows:
[0117] (1) Preparation of positive electrode sheet
[0118] Lithium cobalt oxide (M 3 Including Al), lithium supplement (Li2NiO2), positive electrode conductive agent (conductive carbon black) and positive electrode binder (polyvinylidene fluoride) are mixed according to a mass ratio of 95.563:0.437:1:2, N-methylpyrrolidone (NMP) is added, stirred evenly, and prepared into a positive electrode slurry; the above positive electrode slurry is coated on the first surface and the second surface of the aluminum foil (the coating length of the positive electrode slurry on the first surface of the aluminum foil is greater than the coating length on the second surface), baked, rolled, and a thickness of 100μ m positive electrode sheet; a positive electrode tab welding area of a fixed size is set on the paste coating area of the positive electrode sheet (the size of the positive electrode tab welding area in the width direction of the positive electrode sheet is 20 mm), and the nickel tab is welded in the above-mentioned positive electrode tab welding area by laser; and then, after being passed through a roller, embossing is performed from the first surface to the second surface in the double-sided coating area (avoiding the positive electrode tab welding area) to obtain a second concave portion (first surface) and a convex portion (second surface); the shape of the orthographic projection of the second concave portion and the convex portion on the surface of the positive electrode sheet is a circle;
[0119] Among them, the mass content of element Al in the positive electrode active coating is c1 8965ppm, c4 is 2563ppm, the width of the second recess is 3mm, the depth is 30μm, and the spacing is 3mm; w1 is 7mm, w2 is 27mm, w3 is 15mm, w4 is 7mm, and w5 is 7mm.
[0120] (2) Preparation of negative electrode sheet
[0121] Artificial graphite (secondary particles), silicon-carbon material (the number of primary spherical particles accounts for 0.56 of the total number of primary spherical particles and secondary spherical particles, the average particle size of the primary spherical particles is 4.1 μm, the sphericity s of the primary spherical particles is 0.87, and the mass content of element Si in the silicon-carbon material is 50%), negative electrode conductive agent (carbon nanotubes), negative electrode dispersant (lithium carboxymethyl cellulose) and negative electrode binder (polyacrylic acid) are mixed in a mass ratio of 85:12:0.4:0.1:2.5, and deionized water is added to prepare a negative electrode slurry; the above-mentioned negative electrode slurry is coated on both sides of the carbon-coated copper foil, and after baking and rolling, a negative electrode sheet with a thickness of 110 μm is obtained; a first concave portion (groove) is made on the surface of the negative electrode sheet using a laser;
[0122] Among them, the mass content c2 of element Si in the negative electrode active coating is 6%, the OI value of the negative electrode active coating is 14.3, the width of the groove is 80.5μm, the depth is 20.2μm, the spacing g is 1.2mm; g×s is 1.044, and c4 / c2 is 0.0427.
[0123] (3) Preparation of electrolyte
[0124] In a glove box (H2O<0.01ppm, O2<0.01ppm, Ar atmosphere), ethylene carbonate, propylene carbonate and diethyl carbonate are mixed in a weight ratio of 1:3:6 to obtain an organic solvent; fluoroethylene carbonate, HTCN and lithium hexafluorophosphate are dissolved in the organic solvent to obtain an electrolyte; wherein the mass content c3 of HTCN in the electrolyte is 2.3%; the mass content of fluoroethylene carbonate in the electrolyte is 23%, and the mass content of lithium hexafluorophosphate in the electrolyte is 12.5%;
[0125] Among them, c2 / c3 is 2.6.
[0126] (4) Preparation of batteries
[0127] The positive electrode sheet prepared in step (1), the separator (comprising a polyethylene base film with a thickness of 4 μm, a ceramic layer with a thickness of 2 μm on one side of the base film, a polymethyl methacrylate adhesive layer with a thickness of 0.5 μm on the other side of the base film, and a polyvinylidene fluoride + polymethyl methacrylate adhesive layer with a thickness of 2.5 μm on the outer surface of the ceramic layer) and the negative electrode sheet prepared in step (2) are wound to obtain a winding core; and a battery is obtained through packaging, baking, liquid injection, formation, secondary sealing, sorting and OCV.
[0128] Example 2
[0129] Prepare the battery as follows:
[0130] (1) Preparation of positive electrode
[0131] Lithium cobalt oxide (M 3 Including Al), lithium supplement (Li2NiO2), positive electrode conductive agent (conductive carbon black) and positive electrode binder (polyvinylidene fluoride) are mixed in a mass ratio of 96.71:0.29:1:2, N-methylpyrrolidone (NMP) is added, stirred evenly, and prepared into positive electrode slurry; the above positive electrode slurry is coated on the first surface and the second surface of the aluminum foil (the coating length of the positive electrode slurry on the first surface of the aluminum foil is greater than the coating length on the second surface), baked, rolled, and obtained a thickness of 100μm A positive electrode sheet; a positive electrode tab welding area of a fixed size is provided on the paste coating area of the positive electrode sheet (the size of the positive electrode tab welding area in the width direction of the positive electrode sheet is 15 mm), and the nickel tab is welded in the above-mentioned positive electrode tab welding area by laser; and then, after being passed through a roller, embossing is performed from the first surface to the second surface in the double-sided coating area (avoiding the positive electrode tab welding area) to obtain a second concave portion (first surface) and a convex portion (second surface); the shape of the orthographic projection of the second concave portion and the convex portion on the surface of the positive electrode sheet is a circle;
[0132] Among them, the mass content of element Al in the positive electrode active coating is c1 is 6531ppm, c4 is 1698ppm, the width of the second recess is 2mm, the depth is 20μm, and the spacing is 2mm; w1 is 5mm, w2 is 20mm, w3 is 10mm, w4 is 5mm, and w5 is 5mm.
[0133] (2) Preparation of negative electrode sheet
[0134] Artificial graphite (secondary particles), silicon-carbon material (the number of primary spherical particles accounts for 0.32 of the total number of primary spherical particles and secondary spherical particles, the average particle size of the primary spherical particles is 3.1 μm, the sphericity s of the primary spherical particles is 0.81, and the mass content of element Si in the silicon-carbon material is 50%), negative electrode conductive agent (carbon nanotubes), negative electrode dispersant (lithium carboxymethyl cellulose) and negative electrode binder (polyacrylic acid) are mixed in a mass ratio of 85:12:0.4:0.1:2.5, and deionized water is added to prepare a negative electrode slurry; the above-mentioned negative electrode slurry is coated on both sides of the carbon-coated copper foil, and after baking and rolling, a negative electrode sheet with a thickness of 110 μm is obtained; a first concave portion (groove) is made on the surface of the negative electrode sheet using a laser;
[0135] Among them, the mass content c2 of element Si in the negative electrode active coating is 6%, the OI value of the negative electrode active coating is 12.1, the width of the groove is 60.3μm, the depth is 15.1μm, the spacing g is 0.8mm; g×s is 0.648, and c4 / c2 is 0.0283.
[0136] (3) Preparation of electrolyte
[0137] In a glove box (H2O<0.01ppm, O2<0.01ppm, Ar atmosphere), ethylene carbonate, ethylene carbonate and diethyl carbonate are mixed in a weight ratio of 1:3:6 to obtain an organic solvent; fluoroethylene carbonate, HTCN and lithium salt lithium hexafluorophosphate are dissolved in the organic solvent to obtain an electrolyte; wherein the mass content c3 of HTCN in the electrolyte is 1.5%; the mass content of fluoroethylene carbonate in the electrolyte is 23%, and the mass content of lithium hexafluorophosphate in the electrolyte is 12.5%;
[0138] Among them, c2 / c3 is 4.
[0139] (4) Preparation of batteries
[0140] The positive electrode sheet prepared in step (1), the separator (comprising a polyethylene base film with a thickness of 4 μm, a ceramic layer with a thickness of 2 μm on one side of the base film, a polymethyl methacrylate adhesive layer with a thickness of 0.5 μm on the other side of the base film, and a polyvinylidene fluoride + polymethyl methacrylate adhesive layer with a thickness of 2.5 μm on the outer surface of the ceramic layer) and the negative electrode sheet prepared in step (2) are wound to obtain a winding core; and a battery is obtained through packaging, baking, liquid injection, formation, secondary sealing, sorting and OCV.
[0141] Example 3
[0142] Prepare the battery as follows:
[0143] (1) Preparation of positive electrode
[0144] Lithium cobalt oxide (M 3 Including Al), lithium supplement (Li2NiO2), positive electrode conductive agent (conductive carbon black) and positive electrode binder (polyvinylidene fluoride) are mixed according to a mass ratio of 96.056:0.944:1:2, N-methylpyrrolidone (NMP) is added, stirred evenly, and prepared into a positive electrode slurry; the above positive electrode slurry is coated on the first surface and the second surface of the aluminum foil (the coating length of the positive electrode slurry on the first surface of the aluminum foil is greater than the coating length on the second surface), baked, rolled, and a thickness of 100μ m positive electrode sheet; a positive electrode tab welding area of a fixed size is set on the paste coating area of the positive electrode sheet (the size of the positive electrode tab welding area in the width direction of the positive electrode sheet is 25 mm), and the nickel tab is welded in the above-mentioned positive electrode tab welding area by laser; and then, after being passed through a roller, embossing is performed from the first surface to the second surface in the double-sided coating area (avoiding the positive electrode tab welding area) to obtain a second concave portion (first surface) and a convex portion (second surface); the shape of the orthographic projection of the second concave portion and the convex portion on the surface of the positive electrode sheet is circular;
[0145] Among them, the mass content of element Al in the positive electrode active coating is c1 is 11962ppm, c4 is 5562ppm, the width of the second recess is 1mm, the depth is 10μm, and the spacing is 1mm; w1 is 9mm, w2 is 34mm, w3 is 20mm, w4 is 10mm, and w5 is 10mm.
[0146] (2) Preparation of negative electrode sheet
[0147] Artificial graphite (secondary particles), silicon-carbon material (the number of primary spherical particles accounts for 0.79 of the total number of primary spherical particles and secondary spherical particles, the average particle size of the primary spherical particles is 5 μm, the sphericity s of the primary spherical particles is 0.95, and the mass content of element Si in the silicon-carbon material is 50%), negative electrode conductive agent (carbon nanotubes), negative electrode dispersant (lithium carboxymethyl cellulose) and negative electrode binder (polyacrylic acid) are mixed in a mass ratio of 85:12:0.4:0.1:2.5, and deionized water is added to prepare a negative electrode slurry; the above-mentioned negative electrode slurry is coated on the surfaces of both sides of the carbon-coated copper foil, and after baking and rolling, a negative electrode sheet with a thickness of 110 μm is obtained; a first concave portion (groove) is made on the surface of the negative electrode sheet using a laser;
[0148] Among them, the mass content c2 of element Si in the negative electrode active coating is 6%, the OI value of the negative electrode active coating is 16.9, the width of the groove is 99.6μm, the depth is 30μm, the spacing g is 1.5mm; g×s is 1.425, and c4 / c2 is 0.0927.
[0149] (3) Preparation of electrolyte
[0150] In a glove box (H2O<0.01ppm, O2<0.01ppm, Ar atmosphere), ethylene carbonate, ethylene carbonate and diethyl carbonate are mixed in a weight ratio of 1:3:6 to obtain an organic solvent; fluoroethylene carbonate, HTCN and lithium salt lithium hexafluorophosphate are dissolved in the organic solvent to obtain an electrolyte; wherein the mass content c3 of HTCN in the electrolyte is 3%; the mass content of fluoroethylene carbonate in the electrolyte is 23%, and the mass content of lithium hexafluorophosphate in the electrolyte is 12.5%;
[0151] Among them, c2 / c3 is 2.
[0152] (4) Preparation of batteries
[0153] The positive electrode sheet prepared in step (1), the separator (comprising a polyethylene base film with a thickness of 4 μm, a ceramic layer with a thickness of 2 μm on one side of the base film, a polymethyl methacrylate adhesive layer with a thickness of 0.5 μm on the other side of the base film, and a polyvinylidene fluoride + polymethyl methacrylate adhesive layer with a thickness of 2.5 μm on the outer surface of the ceramic layer) and the negative electrode sheet prepared in step (2) are wound to obtain a winding core; and a battery is obtained through packaging, baking, liquid injection, formation, secondary sealing, sorting and OCV.
[0154] Example 4 Group
[0155] This group of examples is used to verify the influence of the change of "the mass content c1 of the element Al in the positive electrode active coating".
[0156] This group of examples is carried out with reference to Example 1, except that c1 is changed, as follows:
[0157] Example 4a, c1 is 6017 ppm;
[0158] Example 4b, c1 is 14982 ppm.
[0159] Example 5 Group
[0160] This group of examples is used to verify the influence of the change of "the mass content c2 of element Si in the negative electrode active coating".
[0161] This group of examples is carried out with reference to Example 1, except that c2 is regulated by changing the mass content of graphite material and silicon-carbon material in the negative electrode slurry, as follows:
[0162] In Example 5a, artificial graphite, silicon-carbon material, negative electrode conductive agent, negative electrode dispersant and negative electrode binder are mixed in a mass ratio of 91:6:0.4:0.1:2.5; wherein c2 is 3%, c2 / c3 is 1.3, and c4 / c2 is 0.0854;
[0163] In Example 5b, artificial graphite, silicon-carbon material, negative electrode conductive agent, negative electrode dispersant and negative electrode binder are mixed in a mass ratio of 75:22:0.4:0.1:2.5; wherein c2 is 11%, c2 / c3 is 4.78, and c4 / c2 is 0.0233;
[0164] In Example 5c, artificial graphite, silicon-carbon material, negative electrode conductive agent, negative electrode dispersant and negative electrode binder are mixed in a mass ratio of 94:3:0.4:0.1:2.5; wherein c2 is 1.5%, c2 / c3 is 0.65, and c4 / c2 is 0.1709;
[0165] In Example 5d, artificial graphite, silicon-carbon material, negative electrode conductive agent, negative electrode dispersant and negative electrode binder are mixed in a mass ratio of 65:32:0.4:0.1:2.5; wherein c2 is 16%, c2 / c3 is 6.96, and c4 / c2 is 0.016.
[0166] Example 6 Group
[0167] This group of examples is used to verify the impact of changes in the "average particle size of primary spherical particles".
[0168] This group of examples is carried out with reference to Example 1, except that the average particle size of the spherical particles is changed once, as follows:
[0169] Example 6a, the average particle size of the primary spherical particles is 1.3 μm;
[0170] In Example 6b, the average particle size of the primary spherical particles is 6 μm.
[0171] Example 7 Group
[0172] This group of examples is used to verify the influence of the change of "the ratio c2 / c3 of the mass content c2 of element Si in the negative electrode active coating to the mass content c3 of HTCN in the electrolyte".
[0173] This group of examples is carried out with reference to Example 5a and Example 5b, except that c2 / c3 is regulated by changing c3, as follows:
[0174] Example 7a, carried out with reference to Example 5a, except that c3 is 3%, and c2 / c3 is 1;
[0175] Example 7b is carried out with reference to Example 5b, except that c3 is 1.5% and c2 / c3 is 7.33.
[0176] Example 8 Group
[0177] This group of examples is used to verify the impact of changes in "lithium supplements".
[0178] This group of examples is carried out with reference to Example 1, except that no lithium supplement is added or the type of lithium supplement is changed, as follows:
[0179] In Example 8a, no lithium supplement agent is added to the positive electrode slurry, that is, lithium cobalt oxide, positive electrode conductive agent and positive electrode binder are mixed in a mass ratio of 97:1:2;
[0180] In Example 8b, the lithium supplement is replaced with the same mass of Li5FeO4, and the mass content c4 of Fe in the positive electrode active coating is 3844 ppm.
[0181] Example 9 Group
[0182] This group of examples is used to verify the "element M 1 and / or element M 2 The impact of changes in the mass content c4" in the positive electrode active coating.
[0183] This group of examples is carried out with reference to Example 1, except that c4 is regulated by changing the mass content of the lithium supplement agent in the positive electrode slurry, as follows:
[0184] In Example 9a, lithium cobalt oxide, a lithium supplement, a positive electrode conductive agent and a positive electrode binder are mixed in a mass ratio of 96.844:0.156:1:2; wherein c4 is 912 ppm and c4 / c2 is 0.0152;
[0185] In Example 9b, lithium cobalt oxide, a lithium supplement, a positive electrode conductor and a positive electrode binder are mixed in a mass ratio of 95.828:1.172:1:2; wherein c4 is 6923 ppm and c4 / c2 is 0.1154.
[0186] Example 10 Group
[0187] This group of examples is used to verify the "element M 1 and / or element M 2 The impact of changes in the ratio c4 / c2" of the mass content c4 in the positive electrode active coating to the mass content c2 of element Si in the negative electrode active coating.
[0188] This group of examples is carried out with reference to Example 5a and Example 5d, except that c4 / c2 is regulated by changing c4, as follows:
[0189] Example 10a, carried out with reference to Example 5a, except that c4 is 5437, and c4 / c2 is 0.1812;
[0190] Example 10b is carried out with reference to Example 5d, except that c4 is 916 and c4 / c2 is 0.0057.
[0191] Embodiment 11
[0192] This example is used to verify the influence of "whether the second concave portion is located on the surface of the positive electrode active coating on the first surface and whether the convex portion is located on the surface of the positive electrode active coating on the second surface".
[0193] The method is carried out in accordance with Example 1, except that the embossing treatment is performed from the second surface to the first surface, that is, the surface of the positive electrode active coating on the second surface has a second concave portion, and the surface of the positive electrode active coating on the first surface has a convex portion.
[0194] Example 12
[0195] This example is used to verify the influence of “no second concave portion and convex portion on the surface of the positive electrode active coating layer”.
[0196] The same process is carried out as in Example 1, except that no embossing treatment is performed.
[0197] Example 13
[0198] This embodiment is used to verify the influence of "whether the single-sided coating area has a second concave portion".
[0199] The process is carried out in accordance with Example 1, except that embossing is performed on the single-sided coating area and the double-sided coating area (avoiding the positive electrode tab welding area).
[0200] Example 14 Group
[0201] This group of embodiments is used to verify the impact of changes in "w1, w2, w3, w4 and w5".
[0202] This group of examples is carried out with reference to Example 1, except that w1, w2, w3, w4 and w5 are changed as follows:
[0203] Example 14a, w1 is 0.5 mm, w2 is 2 mm, w3 is 2 mm, w4 is 0.5 mm, and w5 is 0.5 mm;
[0204] In Example 14b, w1 is 10 mm, w2 is 40 mm, w3 is 25 mm, w4 is 20 mm, and w5 is 20 mm.
[0205] Embodiment 15
[0206] This example is used to verify the influence of the change of "sphericity s of primary spherical particles".
[0207] The same procedure is carried out as in Example 1, except that s is 0.72.
[0208] Example 16
[0209] This embodiment is used to verify the influence of changing the “type of the first recess”.
[0210] The process is carried out in accordance with Example 1, except that a laser is used to make recessed holes on the surface of the negative electrode sheet, wherein the width of the recessed holes is 80.1 μm, the depth is 25.3 μm, the spacing is 0.5 mm, and g×s is 0.435.
[0211] Example 17 Group
[0212] This group of examples is used to verify the impact of changes in "the value of the number of primary spherical particles to the total number of primary spherical particles and secondary spherical particles".
[0213] This group of examples is carried out with reference to Example 1, except that the number ratio of spherical particles is changed once, as follows:
[0214] In Example 17a, all silicon-carbon materials are primary spherical particles, that is, the number of primary spherical particles accounts for 1 of the total number of primary spherical particles and secondary spherical particles;
[0215] Example 17b, the number of primary spherical particles accounts for 0.13 of the total number of primary spherical particles and secondary spherical particles;
[0216] In Example 17c, the number of primary spherical particles accounts for 0.88 of the total number of primary spherical particles and secondary spherical particles.
[0217] Embodiment 18
[0218] The method is carried out in accordance with Example 1, except that the artificial graphite is primary particles with an average particle size of 6.1 μm.
[0219] Example 19 Group
[0220] This group of examples is used to verify the influence of the change of "the mass content c3 of HTCN in the electrolyte".
[0221] This group of examples is carried out with reference to Example 1, except that c3 is changed, as follows:
[0222] Example 19a, c3 is 0.5%, c2 / c3 is 12;
[0223] In Example 19b, c3 is 5%, and c2 / c3 is 1.2.
[0224] Example 20 Group
[0225] This group of examples is used to verify the impact of changes in the "OI value of the negative electrode active coating".
[0226] This group of examples is carried out with reference to Example 1, except that the OI value of the negative electrode active coating is regulated by changing the average particle size of the secondary particles of the graphite material, as follows:
[0227] Example 20a, the OI value of the negative electrode active coating is 10.2;
[0228] In Example 20b, the OI value of the negative electrode active coating is 29.9.
[0229] The above embodiments all satisfy: the average particle size of the first lithium cobalt oxide particles is 0.3μm-7μm, and the average particle size of the second lithium cobalt oxide particles is 7.5μm-40μm. The above embodiments except embodiment 18 all satisfy: the average particle size of the secondary particles of the graphite material is 6μm-20μm. The above embodiments except embodiment 17a all satisfy: the average particle size of the secondary spherical particles of the silicon-carbon material is 3μm-20μm. The above embodiments except embodiment 12, the convex portions all satisfy: the height is 3μm-40μm, the width is 0.2mm-8mm, and the spacing is 0.5mm-8mm.
[0230] Comparative Example 1
[0231] This group of comparative examples is used to verify the influence of the change of "the mass content c1 of element Al in the positive electrode active coating".
[0232] This comparative example was carried out with reference to Example 1, except that c1 was changed, as follows:
[0233] Comparative Example 1a, c1 is 5271ppm;
[0234] Comparative Example 1b, c1 is 18350 ppm.
[0235] Comparative Example 2
[0236] This comparative example is used to verify the influence of the change of "the mass content c2 of element Si in the negative electrode active coating".
[0237] The method is carried out in accordance with Example 1, except that artificial graphite, silicon-carbon material, negative electrode conductive agent, negative electrode dispersant and negative electrode binder are mixed in a mass ratio of 45:50:0.4:0.1:2.5; wherein c2 is 22.5%.
[0238] Comparative Example 3
[0239] This group of comparative examples is used to verify the influence of the change of the "average particle size d1 of the primary spherical particles".
[0240] This comparative example is carried out with reference to Example 1, except that the average particle size d1 of the spherical particles is changed, as follows:
[0241] Comparative Example 3a, d1 is 0.8 μm;
[0242] In Comparative Example 3b, d1 is 6.5 μm.
[0243] Comparative Example 4
[0244] This group of comparative examples is used to verify the effect of changes in the ratio c2 / c3 of the mass content c2 of element Si in the negative electrode active coating to the mass content c3 of HTCN in the electrolyte.
[0245] This group of comparative examples was carried out with reference to Example 5a and Example 5b, except that c2 / c3 was adjusted by changing c3, as follows:
[0246] Comparative Example 4a was carried out with reference to Example 5a, except that c3 was 5% and c2 / c3 was 0.6;
[0247] Comparative Example 4b was carried out with reference to Example 5b, except that c3 was 0.5% and c2 / c3 was 22.
[0248] Test Case
[0249] (1) Volume energy density test
[0250] The batteries prepared in the examples and comparative examples were tested for volume energy density, and the specific test method is as follows:
[0251] The battery was charged at a current of 0.2C to the charge cut-off voltage (4.48V), then charged at a constant voltage until the current dropped to 0.02C, and then discharged at a current of 0.2C to 3.0V, with the discharged energy recorded as E; the thickness, width and length of the battery were measured and the product of the three was calculated to obtain the volume of the battery recorded as V. The calculation formula for volume energy density is VED = E / V, and the results are recorded in Table 1.
[0252] (2) 45℃ high temperature cycle test
[0253] The batteries prepared in the examples and comparative examples were subjected to a 45°C high temperature cycle test. The specific test method is as follows:
[0254] Place it in a constant temperature room at 45℃ for 2h, charge it to 4.2V at 3.5C constant current, then charge it to 4.48V at 2C constant current and constant voltage, cut off at 0.05C, and place it for 10min; then discharge it to 3.0V at 0.7C, and repeat this cycle for 500 times. When the battery is fully charged at the 500th cycle, its thickness is h1 and its discharge capacity is C1. When the battery is fully charged for the first time, its thickness is h0 and its discharge capacity is C0. Then C1 / C0 is the capacity retention rate after 500 cycles, and (h1-h0) / h0 is the thickness expansion rate after 500 cycles. The results are recorded in Table 1.
[0255] (3) Fast charging test
[0256] The batteries prepared in the examples and comparative examples were subjected to a fast charge test, and the specific test method is as follows:
[0257] Place it in a 25℃ constant temperature box for 2 hours, use 0.2C constant current to discharge to 3.4V, and let it rest for 5 minutes; then use 3.5C constant current to charge to 4.2V, 2.5C constant current to charge to 4.25V, 2C constant current to charge to 4.48V (1.2C end), record the time of 3C constant current charging to 4.2V (the longer the time, the better the fast charging performance), set the blue power to record the time every 1s, and record the results in Table 1.
[0258] Table 1
[0259]
[0260]
[0261] It can be seen from Table 1 that the battery of the present invention has high energy density, excellent cycle stability and fast charging capability compared with the comparative example.
[0262] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A lithium ion secondary battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet and an electrolyte; the charging cut-off voltage of the lithium-ion secondary battery is ≥4.48V; The positive electrode sheet comprises a positive electrode active coating, the positive electrode active coating comprises a positive electrode active material, the positive electrode active material comprises lithium cobalt oxide, the lithium cobalt oxide contains element Al, and the mass content c1 of element Al in the positive electrode active coating is 6000ppm-15000ppm; The negative electrode sheet comprises a negative electrode active coating, the negative electrode active coating comprises a negative electrode active material, the negative electrode active material comprises a silicon-carbon material; the mass content c2 of element Si in the negative electrode active coating is 1.5%-16%; the silicon-carbon material comprises primary spherical particles, and the average particle size of the primary spherical particles is 1 μm-6 μm; The electrolyte includes 1,3,6-hexanetrinitrile; The mass content c3 of 1,3,6-hexanetrinitrile in the electrolyte and the mass content c2 of element Si in the negative electrode active coating satisfy: 0.63≤c2 / c3≤15.
2. The lithium ion secondary battery according to claim 1, wherein 1≤c2 / c3≤7.4; Preferably, 2≤c2 / c3≤4.
3. The lithium ion secondary battery according to claim 1 or 2, wherein: The mass content c1 of element Al in the positive electrode active coating is 6500ppm-12000ppm; and / or, the mass content c2 of element Si in the negative electrode active coating is 3%-11%; And / or, the average particle size of the primary spherical particles is 3 μm-5 μm; And / or, the silicon-carbon material includes a material formed by filling silicon and / or oxidized silicon in pores of porous carbon; And / or, the mass content of element Si in the silicon-carbon material is 30%-80%.
4. The lithium ion secondary battery according to claim 1 or 2, wherein: The positive electrode active coating also includes a lithium supplement agent; Preferably, the lithium supplement comprises a chemical formula of Li 5+x Fe y M 1 z The substance and / or chemical formula of O4 is Li 2±a Ni b M 2 c O2 substances, where -0.5≤x≤5, 0.8≤y≤1.2, 0≤z≤1, M 1 Including at least one of Mo, Nb, Ti, Zr, Ni, Y, Mn, Cu, Mg and Zn; 0≤a≤0.5, 0≤b≤1, 0≤c≤1; M 2 including at least one of Mo, Nb, Ti, Zr, Fe, Y, Mn, Cu, Mg and Zn; Preferably, the element M 1 and / or the element M 2 The mass content c4 in the positive electrode active coating is 900ppm-7000ppm; more preferably 1600ppm-6000ppm.
5. The lithium ion secondary battery according to claim 4, wherein: c4 and the mass content c2 of element Si in the negative electrode active coating satisfy: 0.005≤c4 / c2≤0.19; Preferably, 0.028≤c4 / c2≤0.
093.
6. The lithium ion secondary battery according to claim 1 or 2, wherein: The OI value of the negative electrode active coating is 10-30; preferably 12-17; And / or, the sphericity s of the primary spherical particles is 0.7-1; preferably 0.8-0.
95.
7. The lithium ion secondary battery according to claim 1 or 2, wherein: The outer surface of the negative electrode active coating has a first concave portion, and the spacing g of the first concave portions and the sphericity s of the primary spherical particles satisfy: 0.4≤g×s≤2, wherein the unit of the spacing g of the first concave portions is mm; Preferably, 0.6≤g×s≤1.
5.
8. The lithium ion secondary battery according to claim 7, wherein: The spacing g of the first recess is 0.5 mm-5 mm; And / or, the depth of the first concave portion is 5 μm-40 μm; And / or, the width of the first concave portion is 40 μm-200 μm.
9. The lithium ion secondary battery according to claim 1 or 2, wherein: The silicon-carbon material further comprises a plurality of secondary spherical particles formed by the primary spherical particles; Preferably, the average particle size of the secondary spherical particles is 3 μm-20 μm; Preferably, in the negative electrode active coating, the number of the primary spherical particles accounts for 0.1-0.9 of the total number of the primary spherical particles and the secondary spherical particles; Preferably, the negative electrode active material further includes graphite material.
10. The lithium ion secondary battery according to claim 1 or 2, wherein: The positive electrode sheet includes a positive electrode current collector and the positive electrode active coating located on at least one surface of the positive electrode current collector; the length of the positive electrode active coating located on the first surface of the positive electrode current collector is greater than the length of the positive electrode active coating located on the second surface of the positive electrode current collector; The region where the projection of the positive electrode active coating located on the first surface overlaps with the projection of the positive electrode active coating located on the second surface in the thickness direction of the positive electrode sheet is the double-sided coating region, and the region where the projections do not overlap is the single-sided coating region; The surface of the positive electrode active coating located on the first surface has a second recess, and the surface of the positive electrode active coating located on the second surface has a protrusion; Preferably, the positive electrode sheet includes a positive electrode tab welding region, a pasting region, and a bare foil region, and the second recess and the protrusion are located in the pasting region; Preferably, the positive electrode sheet includes a pasting region, the pasting region includes the double-sided coating region and the single-sided coating region, and the second recess and the protrusion are located in the double-sided coating region; Preferably, the depth of the second recess is 3 μm - 40 μm, the width of the second recess is 0.2 mm - 8 mm, and the pitch of the second recess is 0.5 mm - 8 mm; Preferably, the height of the protrusion is 3 μm - 40 μm, the width of the protrusion is 0.2 mm - 8 mm, and the pitch of the protrusion is 0.5 mm - 8 mm.
11. The lithium ion secondary battery according to claim 10, wherein: The positive electrode sheet includes a positive electrode tab welding region, a pasting region, and a bare foil region, and the pasting region includes the double-sided coating region and the single-sided coating region; The distance from the second recess to the edge of the positive electrode tab welding region is w1, 0 mm < w1 ≤ 10 mm; And / or, the distance from the second recess to the edge of the first side of the pasting region is w2, 2 mm ≤ w2 ≤ 40 mm, and the first side is the side where the positive electrode tab welding region is provided; And / or, the distance from the second recess to the edge of the second side of the pasting region is w3, 2 mm ≤ w3 ≤ 25 mm, and the second side is the side opposite to the side where the positive electrode tab welding region is provided; And / or, the distance from the second recess to the edge of the third side of the pasting region is w4, 0 mm < w4 ≤ 20 mm, and the third side is the side of the pasting region close to the first winding end; And / or, the distance from the second recess to the boundary line between the double-sided coating region and the single-sided coating region is w5, 0 mm < w5 ≤ 20 mm.
Citation Information
Patent Citations
Electrolyte and battery
CN118099518A
Secondary battery and electronic device
CN118173858A
Secondary battery and electronic device
CN119029150A
Battery
CN119029308A
Additive, electrolyte containing additive, and lithium ion battery
WO2023050597A1